146 Association Between Gilts and Sows Body Condition and Reproductive Performance. (7th May 2021) - Huerta, Isaac; Fernandez, Pilar; Vier, Carine M; Aguero, Carmen; Lu, Ning; Blanco, Patricia; Sala, Ruben; Cast, Wayne R; Orlando, Uislei A
Abstract: Our objective was to determine the association between gilts and sows body condition (BC) with reproductive performance. Data from 4, 543 gilts (PIC Landrace, Hendersonville TN) was collected from January 2017 and July 2019 in a 5, 000-sow farm located in Spain. The sow caliper was used to assess BC and was measured in units. Measurements were taken pre-farrowing at d 110 to 113 of gestation and at the day of weaning. Caliper units were used to classify gilt BC at farrowing as thin (< 12), ideal (12–15) and fat (>15). Caliper loss was determined as the caliper units at weaning minus the caliper units pre-farrowing. Response variables included total born, retention rate up to parity 3, total pigs born and total pigs weaned up to parity 3 per gilt served. Tested predictors included BC at farrowing, caliper loss during lactation, number of weaned pigs, lactation length, age at first breeding, wean-to-estrus interval. Data were analyzed with the lm and glm functions from the stats package in R, and final models were selected based on backwards elimination. There was a significant interaction between gilt BC at farrowing and caliper loss in the first lactation. Gilts in ideal condition at farrowing had greater (P < 0.05) retention rate and number of total pigs born and total pigs weaned per gilt served up to parity 3 compared to thin and fat gilts. Fat gilts that lost more than 3 caliper units during lactation had further reduction in retention rate and productivity up to parity 3 compared to fat gilts that lost up to 3 caliper units. For every unit of caliper lost during the first, second, and third lactation, subsequent total born was reduced (P < 0.05) by 0.27, 0.12, and 0.19 pigs, respectively. Results indicated that over-conditioned females are negatively associated with retention and productivity up to parity 3.